2016
DOI: 10.1039/c5ra20684g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different fabrication methods on the chemo-physical properties of silk fibroin films and on their interaction with neural cells

Abstract: In this study, we investigated the influence of processing methods on the chemo-physical properties of silk fibroin (SF) film and on their interaction with neural cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 43 publications
5
30
0
1
Order By: Relevance
“…19.6a), recorded at room temperature, confirmed that the sample obtained by our procedure Fig. 19.6 Chemo-physical properties of in loco produced RSF and NSF solution and films [23] is pure and that the aminoacids composition is in accordance with previous literature report [23,24]. SF conformation influences the biodegradation, mechanical and optical properties of the SF films.…”
Section: Chemo-physical Properties Of Regenerated and Native Silk Fibsupporting
confidence: 83%
See 1 more Smart Citation
“…19.6a), recorded at room temperature, confirmed that the sample obtained by our procedure Fig. 19.6 Chemo-physical properties of in loco produced RSF and NSF solution and films [23] is pure and that the aminoacids composition is in accordance with previous literature report [23,24]. SF conformation influences the biodegradation, mechanical and optical properties of the SF films.…”
Section: Chemo-physical Properties Of Regenerated and Native Silk Fibsupporting
confidence: 83%
“…We have then demonstrated that the application of different fabrication methods to prepare SF films influences the chemo-physical properties of SF films and their interaction with neural cells. In particular, we found that hydrophobic surfaces induce proliferation of astrocytes and neuron adhesion, whereas hydrophilic surfaces promote a remarkable neurite outgrowth [24]. Interestingly, surface properties such as roughness and wettability, mechanical resistance, dissolution and degradation profiles can be affected by fabrication method.…”
Section: Biological Properties Of Silk Films Prepared By Different Mementioning
confidence: 91%
“…Silk fibroin films are typically prepared by casting the aqueous fibroin solution [51]. Other reported techniques include spin-coating [52], vertical deposition [53], and spin assisted layer-by-layer assembly [54]. Silk fibroin films can be easily obtained by casting SF solution on a smooth and clean plate with subsequent natural evaporation or drying under a certain temperature.…”
Section: Structure Design Of Silk Fibroin-based Biomaterialsmentioning
confidence: 99%
“…In their report, a glass coverslip was inserted vertically in the SF solution in an oven at 50 °C; and because of the lateral capillary force and surface tension drive between the fibroin solution and the glass coverslip, silk fibroin solution could be deposited on the glass coverslip and dried to obtain the transparent SF film. However, films prepared by this method showed a non-homogeneous texture, which was caused by the inherent feature of the vertical deposition method [53]. Jiang et al developed an ultrathin SF film (45 ± 5 nm) fabricated by the layer-by-layer assembly technique; the resulting film displayed high elastic modulus and ultimate tensile strength due to its gradual self-reinforcing structure [54].…”
Section: Structure Design Of Silk Fibroin-based Biomaterialsmentioning
confidence: 99%
“…Indeed, the water contact angle value decreases from ≈68.2° for the KerAzA sample to 51.0° for the KerAzAPD red sample. This hydrophilicity value can be related both to the hydrophilic nature of the PD and to the different surface morphology induced by the coating and it is particularly suitable for cells adhesion and growth as also indicated for other biocompatible materials …”
Section: Resultsmentioning
confidence: 99%